Inovasi Layanan Publik Melalui Program CETTAR Berbasis Digital Dalam Mewujudkan Tatanan Pemerintahan Jawa Timur Yang Baik - Muhammad Mughni Labib (Universitas Warmadewa, 2022)
Public service is the most visible measure of government performance. Digital-based public services are an effort to overcome the limitations of public services directly. So that digital innovation is needed in public services to be effective and efficient. This article analyzes public service innovation through the CETTAR program in realizing a good East Java government order. East Java CETTAR is one of the programs from Nawa Bhakti Satya initiated by the Governor of East Java Khofifah Indar Parawansa and the Deputy Governor of East Java Emil Dardak which aims to absorb various aspirations and complaints from the wider community in terms of public services. The Jatim CETTAR application can be accessed through the website and application. This study aims to find out how the digital-based CETTAR program innovation and the obstacles that exist in the implementation of trustworthy government governance. The research method used in this research is library research method. The research was conducted by collecting data through documentation techniques and online data retrieval using content analysis techniques, in this article a literature study and related research and journals were conducted. Based on the findings obtained from this research, it is explained that this program has been running quite well, but there are still obstacles in the form of lack of socialization and half implemented.